Study on bidirectional-charger for electric vehicle applied to power dispatching in smart grid - Fang, Yu; Cao, Songyin; Xie, Yong; Wheeler, Patrick (2016)
It will be one of the most important content to take the electric vehicle batteries as distributed energy storage units which can accept the power dispatching, and now bidirectional charger is the key power electronic device that has been used to connect power grid to the electric vehicle battery. In this paper, a two-stage bidirectional power converter made up of T-type neutral point clamped (NPC) three-phase three-level (TL) AC/DC and dual active bridge (DAB) DC/DC is studied, And the direct power control strategy is adopted to accept power dispatching from power grid. With high reliability, efficiency and high power quality as the goal, a novel space vector modulation (SVPWM) is proposed to avoid the terminal voltage distortion of bridge legs, and the series-parallel-connection DAB converter is presented to further improve efficiency. Finally, experimental results verify the feasibility of circuit topology and control strategy.